Rukhsah Sholat bagi Orang Sakit Perspektif Hadis - Mulia Safrina; Muhammad Taufik (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
This study focuses on the hadiths that discuss the rukhsah prayer for the sick. Every human being in this world will live their life by doing various daily activities. This explains that humans are based on two conditions or circumstances, namely healthy or sick. Every healthy human being will definitely experience a phase where they will feel pain. When someone is sick, it will make it difficult for them to do activities and worship. Rukhsah is a relief, ease, generosity in doing something because of an excuse or in an emergency. Then the question arises what kind of illnesses can prevent someone from praying and getting rukhsah if in that condition. The purpose of this study is to find out how the hadiths are understood about the rukhsah prayer for the sick. Then how is the contextualization of the hadith about the rukhsah prayer for the sick viewed from the current situation and conditions. This study is a library research study using the maudhu`i method in order to find out the understanding by collecting hadiths that have the same theme through their source books and then examining the understanding through the explanation of the hadith. Next, we use a contextual approach to find out the reasons for the emergence of the hadith by referring to its various aspects in detail. The results of this research are that the hadiths are agreed to be of authentic quality by the ulama. From understanding the sharia, there are criteria for illness that allow and prevent someone from carrying out prayers. Certain circumstances have been found that make it possible for someone to pray when they are sick. The cause of lightness in performing prayers is due to the occurrence of one thing or another, such as illness. Illness that befalls a person causes rukhsah for a person in carrying out prayers.